First human safety and effectiveness study of defibrillation with a novel patch wearable cardioverter-defibrillator - Chovanec, Milan; Petrů, Jan; Hála, Pavel; Kralovec, Stepan; Thakkar, Anjali B; Mathews, Kiran; Dinger, Maarten; Ullery, Steven; Eapen, Zubin J; Kumar, Uday N; Neužil, Petr (Europace, 2024)
AIMS: Wearable cardioverter-defibrillators (WCDs) are indicated in patients at risk of sudden cardiac arrest who are not immediate candidates for implantable defibrillator therapy. Limitations of existing WCDs include poor compliance and high false alarm rates. The Jewel is a novel patch-WCD (P-WCD) that addresses these limitations with an adhesive-based design for near-continuous wear and a machine learning algorithm designed to minimize inappropriate detections. This was a first-in-human study of the Jewel P-WCD conducted in an electrophysiology (EP) lab to determine the safety and effectiveness of the device in terminating ventricular tachycardia/ventricular fibrillation (VT/VF) with a single shock. The aim was to evaluate the safety and effectiveness of terminating VT/VF with a single shock using the Jewel P-WCD. METHODS AND RESULTS: This was a first-in-human, prospective, single-arm, single-centre study in patients scheduled for an EP procedure in which VT/VF was expected to either spontaneously occur or be induced. The Jewel P-WCD was placed on consented patients; upon confirmation of VT/VF, a single shock (150 J) was delivered via the device. A group sequential design and Pocock alpha spending function was used to measure the observed proportion of successful VT/VF single-shock terminations. The endpoint was achieved if the lower confidence limit exceeded the performance goal of 62%, using a one-sided lower 97.4% exact confidence bound. Of 18 eligible subjects, 16 (88.9%, 97.4% confidence bound: 65.4%) were successfully defibrillated with a single shock, exceeding the primary endpoint performance goal with no adverse events. CONCLUSION: This first-in-human evaluation of the Jewel P-WCD demonstrated the safety and effectiveness of terminating VT/VF. CLINICAL TRIAL REGISTRATION: URL: https://clinicaltrials.gov/; Unique identifier: NCT05490459.
Keywords: defibrilátory; Humans; Defibrillators; lidé středního věku; elektrická defibrilace; nositelná elektronika; Death, Sudden, Cardiac; Equipment Design; Female; Aged; dospělí; výsledek terapie; senioři; lidé; Electric Countershock; fibrilace komor; Adult; náhlá srdeční smrt; ženské pohlaví; Male; Middle Aged; Treatment Outcome; design vybavení; Ventricular Fibrillation; Wearable Electronic Devices; Sudden cardiac arrest; Ventricular arrhythmia; komorová tachykardie; mužské pohlaví; prospektivní studie; Wearable cardioverter-defibrillator; Tachycardia, Ventricular; Prospective Studies